Influence of blood/anticoagulant ratio and storage temperature on platelet parameters using Cell Dyn Ruby® analyzer - Wolski, Maria Júlia; Moss, Mariane Faria; Kalva-Borato, Danielle Cristyane (Medicina (Ribeirao Preto), 2022)
Introduction: The pre-analytical phase directly influences the laboratory result, such as the method of collection, transport, and storage of biological samples. Therefore, the stability of the biological sample is a crucial and determinant aspect of the quality of results in a clinical laboratory. Studies show that some platelet parameters may suffer alterations in the presence of altered blood/anticoagulant ratio, with increased storage time and/or variations in storage temperature, possibly leading to unrepresentative results. This study aimed to investigate the reliability of platelet parameters regarding the effect of the anticoagulant/blood ratio and storage temperature in samples stored for up to 24 hours after collection using the Cell Dyn Ruby® equipment. Methodology: A total of 351 blood samples were evaluated under different analysis periods: 2, 5, 12, and 24 hours and storage methods: at room temperature (25 ⁰C) and 4 ⁰C, in addition to the analysis of anticoagulant/blood ratio. The Platelet parameters selected were: PLT (total platelet count), MPV (mean platelet volume), PDW (Platelet Distribution Width) and PCT (plateletcrit). The imprecision of the results was evaluated by the CVa (%) within the maximum allowed analytical variation, as well as by the mean difference of the results concerning the baseline sample (2 hours). Results: The total platelet count was the only parameter evaluated that showed reproducibility of results in all conditions analyzed. Regarding the other platelet parameters, it could be observed an imprecision of results emitted by Cell Dyn Ruby® after five hours of storage, both at room and refrigerated temperature. Conclusion: This study demonstrates that pre-analytical factors, such as storage temperature and storage time, can affect the variability of platelet parameters, which may produce erroneous results. Thus, the correct blood/anticoagulant ratio must be respected to avoid the late processing of the sample.